Характер изменчивости компонентного состава 7S и 11S глобулиновых белков у гибридов F₄ сои - Адамовская, В.Г.; Молодченкова, О.О.; Сичкарь, В.И.; Картузова, Т.В.; Безкровная, Л.Я.; Лаврова, Г.Д. (Фактори експериментальної еволюції організмів, 2014)
Aims. Glycinin (11S globulin) and β-conglycinin (7S globulin) are important seed storage proteins in soybean. The objective of this work was to analysis of variation in the electrophoretic patterns of 11S and 7S globulins of F₄ hybrids of soybean seed. Methods. 7S and 11S globulins were separated by method, which was developed in the Laboratory of Plant Biochemistry (Patent # 42181). The pictures of the 11S and 7S globulins were got with SDS-PAGE electrophoresis. Results. It was established, that part of 23 families of hybrid combination (Vilana × [Yurievka × Izumrudnaya]) have the paternal or maternal component composition of glycinin, β-conglycinin and summary globulins. Some families of studied hybrid combination of soybean have the specific, peculiar only by him, component composition of globulins. Conclusions. The got results testify that component composition of 7S and 11S globulins in the soybean F₄ hybrids is polymorphic. Further researches of these indexes on the soybean F₅ hybrids will allow study the character of inheritance of component composition of 11S and 7S globulins, which responsible for quality of products from soybean. The results provide a basis to improve soybean protein quality and breed high quality variety.

Key words: Glicine max L., 11S globulin, 7S globulin.